#TITLE_ALTERNATIVE# - IRAWAN ZULKARNAIN (NIM 12203051), DODY
The reservoir pressure and the flowing well bore pressure will decline continuously during the production of reservoir fluids. In the case of reservoir pressure above the bubble point pressure, when the decreasing well bore pressure has passed below the bubble point pressure, then the dissolved gas in oil will be liberated as gas phase in the form of bubbles and flow with oil. This condition occurs when the saturation value of gas has passed its critical value, at this time there are gas phase and oil phase flow in the reservoir. When the pressure away from the well bore is still higher than the bubble point pressure, then in the reservoir there would be two section of flow, which are two phase flow in the section that close to the well bore, and single phase flow in the other section up to the reservoir boundary. This condition were modeled by Vogel, and other researchers, where most of them assuming that the initial reservoir pressure equal to or less than the bubble point pressure. Therefore, an IPR curve is needed to depict reservoir ability in producing fluid, in this condition. There are some IPR equations that have been published and accepted in general, like Gilbert4,Vogel9, Sukarno10, etc. There are also IPR equation for prediction purposes that has been published by Standing8, Eckmier5, and Sukarno10. These equations were developed with assumption of below bubble point pressure. This Paper investigates the influence of different bubble point pressure, the study also expected to give the new IPR curve forecasting equation referred to the given condition. The study was done by CMG simulator, the study also using the same rock data and reservoir fluid as those which used by Vogel9 in conducting its research.